Triggered Abuse: How and Why Leaders with Narcissistic Rivalry React to Follower Deviance - Iris K. Gauglitz; Birgit Schyns (Journal of Business Ethics, 2024)
Abstract Previous research has shown that leaders' narcissistic rivalry is positively associated with abusive supervision. However, it remains unclear when and how leaders high in narcissistic rivalry show abusive supervision. Building on trait activation theory and the Narcissistic Admiration and Rivalry Concept (NARC), we assumed that leaders high in narcissistic rivalry particularly show abusive supervision in reaction to follower workplace deviance due to their tendency to devaluate others. We argued that leaders' injury initiation motives explain why leaders high in narcissistic rivalry react with abusive supervision when experiencing organization-directed or supervisor-directed deviance. However, this should not be the case for coworker-directed deviance, as leaders high in narcissistic rivalry are less likely to find such behavior violates their internal norms. We conducted two studies. In the first study, we provided participants with experimental vignettes of follower workplace deviance. In the second study, we used a mixed-methods approach and investigated leaders' autobiographical recollections of follower workplace deviance. We found a positive direct effect of leaders' narcissistic rivalry across both studies. Leaders high in narcissistic rivalry showed abusive supervision (intentions) in response to organization-directed deviance (Studies 1 and 2) or supervisor-directed deviance (Study 1), but not in response to coworker-directed deviance (Studies 1 and 2). Leaders' injury initiation motives could in part explain this effect. We discuss findings in light of the NARC and devaluation of others and derive implications for theory and practice.
Keywords: 330; Narcissism; Abusive supervision; Workplace deviance; Injury initiation motives